IMPLEMENTASI KEGIATAN MENTORING DALAM PENGUATAN NILAI-NILAI KEAGAMAAN KELAS 10 SMAN 04 KOTA BIMA - Rati Puspitasari; Nasaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Abstrack This study aims to describe the implementation of leadership activities in strengthening religious values ​​in 10th grade students at SMAN 4 Kota Bima. Strengthening religious values ​​is an important aspect in shaping the character of the young generation with integrity and noble morals. Through leadership activities, students are not only trained to have leadership skills, but are also expected to be able to internalize religious values ​​such as honesty, responsibility, empathy, and cooperation in everyday life. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions with validation using triangulation of sources and techniques. The results of the study indicate that leadership activities at SMAN 4 Kota Bima, such as Mentoring and Saturday-Sunday Camp (Persami) with religious themes, play a significant role in fostering religious attitudes, responsibility, and independence of students. In addition, the role of Islamic Religious Education (PAI) teachers and the support of the school greatly influence the success of religious character formation in the school environment. Leadership activities create a religious learning atmosphere, accustom students to behave according to religious teachings, and encourage them to become leaders with integrity and a high social spirit. Despite challenges such as limited student participation and resources, leadership activities at SMAN 4 Kota Bima have proven effective as a means of strengthening religious values ​​and can be used as a model for spiritual-based character development in secondary schools. Kywoard: leadership, religious values, character education, SMAN 4 Kota Bima, student leadership.